Pengembangan LKPD Mengenal Huruf Alfabet dan Coding Untuk Siswa Kelas 1 Sekolah Dasar - Astutik, Leny Suryaning; Ana, Ria Fajrin Rizqy; Ulum, Bachrul; Jadmiko, Rahmad Setyo (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
Introduction to the alphabet and coding for grade 1 elementary school students is important. This is because the alphabet is the main foundation in basic reading and writing. Meanwhile, studying coding for elementary school age sharpens logic and keeps up with developments in technological sophistication. The aim of this research is to produce LKPD (Learner Worksheets) that are valid and practical. The development of this LKPD uses the ADDIE development model. The research results show that the average validity of LKPD experts, material experts and learning experts is 94% in the